Evaluación rápida de las aves de la parte baja de la cuenca del río Anamichú, municipio de Rio Blanco – Tolima (2016)
In May and June 2008 we conducted a rapid assessment of the non-previously studied low part of the Anamichú river basin. Field surveys were done in three sites, principally relictual forests and agricultural areas. A total of 106 species of birds were registered, among which there are six new distributional records to Tolima department, two are colombian endemic, ten semi–endemic and one species of interest to Colombia. The general composition was primarily represented (80%) by birds of wide tolerance, asociated with open areas (ecological cathegories II and III). This directly reflects the presence of agriculture landscapes with few forest covering. The most number of forest birds and two endemic species were recorded at the highest zone of the study, closeto the Las Hermosas National Park. This results suggest the study zone could represent an interest area for conservation and point out the need of new ornithological surveys